TEORI PEMAHAMAN HADIS HASAN - Nurliana Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Hasan's Hadith is a Hadith whose sanad is to be continued, by a fair narrator but is not very strong in his memory, and is protected from anomalies and diseases. To eliminate the mistake between the Sahih Hadith and the Hadith Hasan, the most important thing about this limitation, is that justice in the Hadith Hasan is carried on the Sahih Hadith attached to the narrators who are really strong in their memories. But both are free from incongruity and disease. Both can be used as evidence and their contents can be used as reinforcement in taking / referral. Hasan's Hadith is one of the discussions of this paper which according to the scholars also differed in its definition. This difference occurs pbecause there are some scholars of Hadith who classify Hasan Hadith as a Hadith who occupies a position between the Hadith and the Hadith Da'eef. But there are also those who include it as part of the Hadith Da'eef that can be used as proof of the hadith.